Suffering: An Eastern Patristic Timetic Perspective - Moldovan, Sebastian (Religions, 2024)
The essay explores the theme of suffering from an Eastern Patristic perspective, focusing on its spiritual and communal dimensions. It draws on the works of Maximos the Confessor, a famous 7th-century Byzantine theologian, particularly on his Amiguum 8. Maximos presents suffering not only as an inevitable consequence of the lapsarian human condition but also as a providential opportunity for moral and spiritual growth. Through suffering, individuals can reorient themselves towards God, fostering virtues like compassion and gratitude. This kenotic love, modeled after Christ’s sacrificial love, reveals the inherent dignity and equality of all human beings. Maximos’ perspective is at odds with the modern technological and political systems, which often depersonalize care and diminish the role of spiritual transformation, especially in the end-of-life context. The essay suggests that, while technological advancements address suffering, they may overlook the spiritual truth that suffering reveals—a truth central to human dignity and salvation. This perspective invites further exploration into the interplay between Christian theology, suffering, and modern biopolitics.